Building a new heritage tourism, culture and identity in the new Europe : volume 3 - Ashworth, Gregory J. 1941-2016; Larkham, P. J. 1960- (Routledge library editions: Tourism, 2013)
At the heart of the European debate lies the tension between the idea of European unity and individual state identities and nationalisms. This volume provides an insight into this dichotomy by exploring the role of heritage in the new Europe. The main theme of this book is that a number of possible heritages can be shaped from the European past depending on the purposes for which they are intended. Through different methods of management intervention, heritage can fulfil a variety of functions, becoming a major commercial resource in the form of the tourism industry, or enlisted in the creation and maintenance of place identities. Leading contributors look at different perceptions of heritage by different cultures, and the social and political consequences of heritage planning. The nature of heritage planning for emerging, spatially fragmented state structures is also discussed